Paranasal Sinus Involvement in Metastatic Carcinoma - Abi-Fadel, Francois; Smith, Peter R.; Ayaz, Asim; Sundaram, Krishnamurthi (Journal of Neurological Surgery Reports, 2012)
Metastatic carcinoma involving the paranasal sinuses is uncommon. One hundred-sixty seven cases have been published in the literature since 1951. Symptoms, signs, and rhinoscopic and imaging findings are often nonspecific, and the diagnosis may be missed for considerable time. Therefore, a high level of suspicion is warranted in patients with known malignancies presenting with persistent or recurrent rhinosinusitis or facial complaints.
Keywords: metastatic carcinoma; paranasal sinuses; paranasal sinus metastases; sinusitis